Halal virtual inspection web-based system (halal-vi) / Mohammad Hazim Ahmad Nasre - Ahmad Nasre, Mohammad Hazim (2022)
Technology nowadays is very easily accessible by any user regardless of time, place and age. In addition, the COVID-19 pandemic situation that has hit the whole country now has caused many people to face difficulties, among of them are the traders, who want to open a business or continue their business. For those who want to start a business especially those who need Halal Certificate (HC) certification, they need to submit a form and wait for the auditing process or more simply called inspection. The inspection process is now taking quite a long time because during this pandemic season, the public is not allowed out because of the Movement Control Order which has been directed by the government to reduce the risk of the virus spreading.